Understanding Nigeria's security through import control under the military, 1972-1999 (2020)
The military as an institution has played important roles in the history of Nigeria since 1966 when it intervened in the country's politics. Scholars of various disciplines such as political Science, history, philosophy, sociology and economics through their works, have examined the role of the military in governance, as well as, the management of the country's economy. Foreign policy formulation, the Civil War, creation of more States which served as transition from regionalism are typical examples of the inputs of the military to the country's nation building project. Similarly, scholars have interrogated the roles of the military in the country's history through population census, management of foreign reserves, and introduction of new currencies as well as the country's infrastructural expansion. However, comprehensive intellectual attention has not been paid to the role the military, as an institution, has played in Nigeria' s import control. It is against this backdrop that this paper interrogates the nature of Nigeria's import control under the military. The paper argues in its conclusion that import control under the military reveals the extent to which the military managed the country's economy.